ANALISIS KEBIASAAN BERBAHASA IBU DI RUMAH TERHADAP PENGGUNAAN BAHASA INDONESIA DI KELAS 2 SDN 26 MENTATAI BELOYANG - Oktaviana, Oktaviana; Mastiah, Mastiah; Suyatmin, Suyatmin (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2024)
Abstract: Research faces students' difficulties in using Indonesian and students tend to use their mother tongue at school. The aim of the study was to determine the habits of mother tongue at home and the influence of students' mother language on the use of Indonesian at school. The research method uses a qualitative descriptive analytic approach. The research subjects were grade 2 Public Elementary School 26 Mentatai Beloyang. The object of research is the habit of mother tongue at home on the use of Indonesian in class. Data collection techniques using observation and interviews. Date analysis includes data reduction stage. Presentation of data and drawing conclusions. Checking the validity of data using technical triangulation. The results of research on mother tongue habits on the use of Indonesian in class 2 of Public Elementary School 26 Mentatai Beloyang found that on average students still use their mother tongue a lot during the learning process in class. Students are not used to using Indonesian in communicating or studying, so students are more dominant in using their mother tongue as the language of everyday communication at school. Conclusions from mother tongue habits at home on the use of Indonesian in class 2 0f SD Negeri 26 Mentatai Beloyang that children still use their mother tongue in class.Keywords: Habits, Mother Language, Elementary School Students.Â Abstrak: Penelitian ini didasari oleh siswa kesulitan dalam penggunaan bahasa Indonesia dan siswa cenderung menggunakan bahasa ibu di sekolah. Tujuan penelitian ini mengetahui kebiasaan siswa dalam berbahasa ibu di rumah dan pengaruh bahasa terhadap penggunaan bahasa Indonesia di sekolah. Metode penelitian menggunakan kualitatif dengan pendekatan deskriptif analitik. Subjek penelitian siswa kelas 2 SD Negeri 26 Mentatai Beloyang. Objek penelitian kebiasaan berbahasa ibu di rumah terhadap penggunaan bahasa Indonesia di kelas. Teknik pengumpulan data menggunakan observasi dan wawancara. Analisis data meliputi tahap reduksi data. Penyajian data menggunakan triangulasi teknik. Hasil penelitian tentang kebiasaan berbahasa ibu terhadap penggunaan bahasa Indonesia di kelas 2 SD Negeri 26 Mentatai Beloayang diketahui masih rata-rata siswa masih banyak menggunakan bahasa ibu pada saat proses pembelajaran di kelas. Siswa belum terbiasa menggunakan bahasa Indonesia dalam berkomunikasi maupun belajar, sehingga siswa lebih dominan menggunakan bahasa ibu sebagai bahasa komunikasi sehari-hari di sekolah. Kesimpulan dari kebiasaan berbahasa ibu di rumah terhadap penggunaan bahasa Indonesia di kelas 2 SD Negeri 26 Mentatai Beloyang bahwa anak-anak masih menggunakan bahasa ibu di kelas.Kata Kunci: Kebiasaan, Berbahasa Ibu, Siswa Sekolah Dasar.